THE IMPORTANCE OF USING MULTIPLE ANALYSES TECHNIQUES TO DETERMINE THE PHYSICAL CONDITION OF THE WATERLOGGED WOOD NEAR THE CORRODED PARTS - Kilic, Asli Gokce; Kilic, Namik; Akgun, Cem (SLOVAK FOREST PRODUCTS RESEARCH INST, 2021)
In this study, three samples taken from the planks of the Yenikapi 29 shipwreck were analysed. Firstly, the maximum water content (MWC) and basic density values of the samples were calculated. MWC of the IK13-1 was 164% and the MWC of the SK6-1 was 87%. Because of these low MWC values, samples could be classified as non-degraded. When the SEM images of these two samples were examined, it was understood that the IK13-1 sample was non-degraded but the SK6-1 sample was penetrated with corrosion product and could not be classified as non-degraded. With these analyses, the XRF method was used to measure the iron amounts of the samples. The iron amount of the SK6-1 was 32.3% and the corrosion accumulation in this sample was also proved with XRF. In order to avoid incorrect results, multiple analysis techniques should be used for determining the physical condition of the waterlogged wood near the corroded parts.
Keywords: Basic density; maximum water content; SEM; waterlogged wood; Yenikapi shipwrecks; ARCHAEOLOGICAL WOOD; PRESERVATION; STATE; SHIPWRECKS; Materials Science